Antioxidant, thrombolytic, cytotoxic and membrane stabilizing activities and fatty acid composition of Acmella Calva (DC.) Flower (Bangladesh Journal of Botany, 2025)
In the present study, crude methanolic extract (CRME) of A. calva flower along with its n-hexane (HSF), ethyl acetate (EASF), dichloromethane (DCMSF) and aqueous (AQSF) soluble fractions were subjected to antioxidant, thrombolytic, cytotoxic and membrane stabilizing activities. Fatty acid composition of the n-hexane extract was analysed by gas chromatography-flame ionization detector. None of the extracts showed any cytotoxicity against both carcinoma (HeLa) and normal cell lines (Vero and BHK-21). EASF scavenged the DPPH free radical most actively with IC50 value of 35.05 μg/ml. CRME and HSF showed profound membrane stabilizing activity by protecting human erythrocyte cell against hypotonic solution-induced and heat-induced lysis. CRME showed the highest (46%) clot lysis. Stearic acid (51.11%) and palmitoleic acid (39.38%) were found in the highest amount in both bound and free form of fatty acid, respectively. The observation from this study indicates the possibility of A. calva to be a good source of different bioactive phytochemicals.Bangladesh J. Bot. 54(3): 433-439, 2025 (September)